Serious infections of soft parts: general analytical study of 41 cases. - Torterolo, Edgardo; Morelli Brum, Raúl; Silva, Celso (Cirugía del Uruguay, 1977)
The authors review 41 cases of serious infections of soft parts, their frequency has increased within the last few years due to the fact that more complex patients, - with lower defences in local sector or in E. TORTEROLO Y COL. general, are now being treated, thus increasing the possibility of invasion by germs which had, until now, been considered as having low pathogenic potency and being generalJy symbiotic. The only treatment that may save the patients' life is surgery, with wide incisions and ample resection of devitalized tissues. Death-rate is connected with sepsis and its multiviséeral repercussions.